The Determination of Yarn Supplier by Using the Weight Product Method. (November 2020) - Indriyani, Fintri; Irfiani, Eni; Schaduw, Frans Edward; Anwar, Syaiful; Hidayat, Rahmat
Abstract: The Upstream Supply Chain Management is the initial component of the supply chain where the company gets raw materials from suppliers for the production process. This process is very important in the sustainability of a company's production. The obstacle experienced at this stage is how the company decides which suppliers to choose from the many suppliers who want to offer their products. Also, it is experienced by PT. Mayer Indah Indonesia, which currently has 14 prospective suppliers, each of which has a different weight based on the assessment criteria of the company. The purpose of this study is to assist companies in making decisions to determine the best suppliers by using the Weight Product (WP) method, while the selection criteria are based on price, quality and the delivery accuracy. The results of the study can be implemented by the company to determine the right supplier in accordance with the criteria that have been required.